2014
DOI: 10.1098/rsif.2013.1092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic analysis of the search behaviour ofCaenorhabditis elegans

Abstract: A central question in movement research is how animals use information and movement to promote encounter success. Current random search theory identifies reorientation patterns as key to the compromise between optimizing encounters for both nearby and faraway targets, but how the balance between intrinsic motor programmes and previous environmental experience determines the occurrence of these reorientation behaviours remains unknown. We used high-resolution tracking and imaging data to describe the complete m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 47 publications
3
69
0
Order By: Relevance
“…This form of public goods production, which may be incidental to the foraging behavior of the worms, is qualitatively different from situations in which the good production is associated only with the explicit metabolic cost of chemical synthesis of the good, a mechanism often at play in microbial systems (6,(8)(9)(10), which lack complex behaviors. In contrast, the mechanism of public goods production that we describe here could be associated with neurobehavioral traits, such as exploration-exploitation strategies (18,19,29,(40)(41)(42) or the use of spatial memory (42,43), in addition to potential metabolic costs associated with carrying the bacteria (37,38). Moreover, C. elegans also appear to be capable of dispersing Dictyostelium discoideum spores (44), another food source; given that D. discoideum themselves farm bacteria (7), we anticipate a rich set of multitrophic level dynamics and niche partitioning to emerge in multispecies interactions involving the kind of effects that we have uncovered here.…”
Section: Discussionmentioning
confidence: 63%
“…This form of public goods production, which may be incidental to the foraging behavior of the worms, is qualitatively different from situations in which the good production is associated only with the explicit metabolic cost of chemical synthesis of the good, a mechanism often at play in microbial systems (6,(8)(9)(10), which lack complex behaviors. In contrast, the mechanism of public goods production that we describe here could be associated with neurobehavioral traits, such as exploration-exploitation strategies (18,19,29,(40)(41)(42) or the use of spatial memory (42,43), in addition to potential metabolic costs associated with carrying the bacteria (37,38). Moreover, C. elegans also appear to be capable of dispersing Dictyostelium discoideum spores (44), another food source; given that D. discoideum themselves farm bacteria (7), we anticipate a rich set of multitrophic level dynamics and niche partitioning to emerge in multispecies interactions involving the kind of effects that we have uncovered here.…”
Section: Discussionmentioning
confidence: 63%
“…This tendency has, however, been observed in the nematode Caenorhabditis elegans when crawling on a surface and when swimming in water in the absence of external stimuli [165][166][167][168]. Salvador et al [168] also reported that meansquare displacements grew super-diffusively (as t 1.37 ) rather than ballistically (as t 2 ), as was expected for diffusivity growing linearly over time. This expectation was, however, for continuous movements; C. elegans have intermittent movements such that bouts of continuous movement are occasionally interrupted by pauses.…”
Section: Lévy Walks Could Results From Variation In Individual Correlamentioning
confidence: 78%
“…Decrease in environmental asymmetry hampers but does not prevent the switch from uncertainty to intense locomotion Movement strategies are believed to arise from a balance between intrinsic and extrinsic mechanisms (Salvador et al, 2014). We hypothesize that the rotational searching behaviour of Lymnaea was initially determined by expectations developed from previous environmental experiences: a recent presence of water suggests a high probability of water remaining, as occurs when snails face dry surfaces and air in their natural ecology.…”
Section: Risky Decision Making By Snails In a Vital Situationmentioning
confidence: 99%